Experimental Realization of Optimal Time‐Reversal on an Atom Chip for Quantum Undo Operations. Issue 12 (13th October 2022) - Mastroserio, Ivana; Gherardini, Stefano; Lovecchio, Cosimo; Calarco, Tommaso; Montangero, Simone; Cataliotti, Francesco S.; Caruso, Filippo
Abstract: The authors report the use of the dressed chopped random basis optimal control algorithm to realize time‐reversal procedures. The latter are aimed for the implementation of quantum undo operations in quantum technology contexts as quantum computing and quantum communications. The last performed operation can be time‐reversed via the undo command so as to perfectly restore a condition in which any new operation, chosen by the external user, can be applied. By generalizing this concept, the undo command can also allow for the reversing of a quantum operation in a generic time instant of the past. Here, thanks to optimal time‐reversal routines, all these functionalities are experimentally implemented on the fivefold F = 2 $F=2$ Hilbert space of a Bose–Einstein condensate of non‐interacting 87 Rb atoms in the ground state, realized with an atom chip. Each time‐reversal transformation is attained by designing an optimal modulated radio frequency field, achieving on average an accuracy of around 92% in any performed test. The experimental results are accompanied by a thermodynamic interpretation based on the Loschmidt echo. These findings are expected to promote the implementation of time‐reversal operations in a real scenario of gate‐based quantum computing with a more complex structure than the five‐level system considered here. Abstract : It is experimentally demonstrated that the undo of an operation, belonging to a past computational routine, is possible also in quantum regimes. By exploiting the optimal control algorithm based on the dressed chopped random basis method, time‐reversal transformations are performed on a Bose–Einstein condensate within an atom chip. The successful results could be applied on a real gate‐based quantum computer.